"AN INVESTIGATION INTO PRONUNCIATIONOF ENGLISH VOWELS EXPERIENCED BYTHE THIRD-YEAR ENGLISH-MAJOR STUDENTS AT DUY TAN UNIVERSITY" - Đoàn Thị Thanh Tâm (2012)
Introduction; Literature review and theoretical background; Methods and proceddures; ...